Duration of breastfeeding, age at introduction of complementary foods and allergy-related diseases: a prospective cohort study - Ekelund, Louise (Int Breastfeed J, 2021)
BACKGROUND: The influences of breastfeeding and infant diet in the prevention of allergy-related diseases are uncertain and many of the studies conducted on the topic are limited by methodological challenges. Our aim was to assess whether the duration of breastfeeding and age at complementary food introduction affected the prevalence of asthma, wheeze, allergic rhinoconjunctivitis (ARC) and eczema at two and six years of age. METHODS: We used information gathered between 2000 and 2014 through questionnaires in the Prevention of Allergy among Children in Trondheim (PACT) study, a prospective cohort study in Trondheim, Norway. The current study includes 6802 children who submitted questionnaires detailing breastfeeding duration and or age at introduction to complementary foods, as well as at least one of the child health questionnaires completed at two and six years of age. Adjusted odds ratios (aORs) were calculated for each combination of exposure and outcomes and sensitivity analyses were performed to assess the possible influence of recall bias and reverse causality. RESULTS: The mean duration of breastfeeding was 11 months (SD 5.6) in this study population and 5695 of 6796 (84%) infants had been breastfed for at least 6 months. We did not find any conclusive preventative effect of longer breastfeeding on parental reported doctor-diagnosed asthma, aOR 0.79 (95% CI 0.51, 1.21). However, at 6 years of age we observed a reduction in the less strictly defined outcome wheeze, aOR 0.71 (95% CI 0.53, 0.95). Longer breastfeeding was associated with a reduced risk of ARC at 2 years, aOR 0.65 (95% CI 0.49, 0.86), with a continued protective trend at 6 years, aOR 0.77 (95% CI 0.58, 1.04). CONCLUSIONS: Longer breastfeeding resulted in a reduced risk of wheeze and a trend towards a protective effect on ARC up until school age. No conclusive associations were seen between the duration of breastfeeding or age at introduction to complementary foods and prevention of asthma, wheeze, ARC and eczema. TRIAL REGISTRATION: The trial is registered in Current Controlled Trials as ISRCTN28090297. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13006-020-00352-2.